2019
DOI: 10.1002/hed.25629
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor budding, tumor‐stroma ratio, cell nests size, and stroma type in laryngeal and pharyngeal squamous cell carcinomas

Abstract: Background Despite immune microenvironment of head and neck squamous cell carcinoma (HNSCC) has been studied, there are no sufficient data on the role of tumor stroma factors. The aim of the study was to explore the prognostic and predictive role of these factors in a large series of HNSCC. Methods This is a retrospective study of 266 patients with laryngeal and pharyngeal SCC. Clinical data were correlated with the following histological parameters: tumor‐stroma ratio (TSR), tumor budding activity (BA), cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
64
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 27 publications
10
64
1
Order By: Relevance
“…2,8,9,11,12,20,27,34,40,45,48,54 This definition is in accordance with the recent recommendation by the International Tumor Budding Consensus Conference (ITBCC 2016) in colorectal cancer, 55 and also agrees with studies on other cancers. 2,8,9,11,12,20,27,34,40,45,48,54 This definition is in accordance with the recent recommendation by the International Tumor Budding Consensus Conference (ITBCC 2016) in colorectal cancer, 55 and also agrees with studies on other cancers.…”
Section: Evaluation Of Tumor Buddingsupporting
confidence: 87%
See 4 more Smart Citations
“…2,8,9,11,12,20,27,34,40,45,48,54 This definition is in accordance with the recent recommendation by the International Tumor Budding Consensus Conference (ITBCC 2016) in colorectal cancer, 55 and also agrees with studies on other cancers. 2,8,9,11,12,20,27,34,40,45,48,54 This definition is in accordance with the recent recommendation by the International Tumor Budding Consensus Conference (ITBCC 2016) in colorectal cancer, 55 and also agrees with studies on other cancers.…”
Section: Evaluation Of Tumor Buddingsupporting
confidence: 87%
“…Of note, our recent systematic search found 16 studies on tumor budding in OSCC and the meta-analysis confirmed the significance of tumor budding in prognostication of lymph node metastasis and survival. Similar results on the significance of tumor budding were reported in an independent cohort of hypopharyngeal SCC by Imai et al, 11 and also for pharyngeal SCC by Karpathiou et al 34 Specifically, identification of high intensity of tumor budding in HNSCC has been associated with metastasis to cervical lymph nodes. 33 In laryngeal cancer, Sarioglu et al 8 were the first to evaluate tumor budding in HNSCC and they reported the prognostic power of tumor budding to predict distant metastasis in laryngeal carcinoma.…”
Section: Tumor Budding As a Simple Promising Prognostic Marker In Hsupporting
confidence: 83%
See 3 more Smart Citations